An extended TODIM-PROMETHEE method for waste-to-energy plant site selection based on sustainability perspective. (1st August 2018) - Wu, Yunna; Wang, Jing; Hu, Yong; Ke, Yiming; Li, Lingwenying
Abstract: The waste-to-energy (WtE) project has attracted much attention from the society mainly because of the characteristic of environmental friendliness. And plant site selection occupies a prominent position during the whole life cycle of waste-to-energy project. In consideration of the ambiguity of subjective judgments of decision makers (DMs) and the compensation problem existing in decision process, we build a framework for WtE plant site selection decision utilizing a novel method with triangular intuitionistic fuzzy numbers (TIFNs). First of all, the criteria for optimal WtE plant siting are determined based on extended sustainability theory including four perspectives of economic, environment, society, and technology to meet the demand of current social development. Then, the TIFNs and the triangular intuitionistic fuzzy weighted geometric (TIFWG) operator are applied to describing the indefinite information and completing the conversion, so that the uncertainty and hesitation of decision information can be well expressed. Furthermore, the extended TODIM (an acronym in Portuguese of interactive and multiple attribute decision making) method in conjunction with PROMETHEE-II (Preference Ranking Organization Method for Enrichment Evaluations) method is utilized to rank the alternatives, which makes this framework more practical and applicable. Finally, a case from China certifies the validity of the proposed framework. Highlights: An extended TODIM-PROMETHEE method was employed to select the optimal WtE site. Evaluation index system for the WtE plant site selection was built. The optimal WtE site was selected due to its highest net flow. Sensitive analysis was performed to verify the robustness of decision result.